Justifying sustainable development: a continuing ethical search - Rolston, Holmes, 1932-2025, author; Centre for World Dialogue, publisher (Colorado State University. Libraries, 2002)
Five criticisms of sustainable development are examined: (1) Is it moral umbrella? Or cover-up? (2) Do we have duties to future generations? (3) How far do rich Americans have duties of justice or benevolence to the developing world? (4) Is producing more, even sustainably, an ultimate good? (5) Do we seek sustainable development or a sustainable biosphere? Finally, if sustainability is justified, ought we to enforce it?
Keywords: human needs; conservation; sustainable development; environmental ethics; justice; ecological integrity